PENDIDIKAN ISLAM DAN PERSONALITI DEVELOPMENT (Studi Pengembangan Kepribadian Siswa di SMAN 1 Karangbinangun Lamongan) - Rokim Rokim (Akademika, 2019)
research in this thesis is motivated by the reality in the field that shows the influence of the development of Islamic education on the personality of students. The position of Islamic religious educatin as compulsoy subjects in schools is expected to contibute sufficiently in improving the morale or behavior of learners seems difficult to realize. Therefore it is necessary to hold the development of Islamic religious education as an alternative to overcome the problems that exist in Islamic religious education. For that this thesis is written with thw title of ”development of Islamic religious education in an effort to improvethe quality of student personality”. The purpose of this study is to determine the development of Islamic religious education in an effort to improve the quality of student personality, supporting factors and inhibiting the development of Islamic religious education, and how to overcome the factors hindering the development of Islamic religious education. This research uses descriptive qualitative research approach. The subjects in this research are principal, Pai teacher and student SMAN 1 Karangbinangun. While data collection technique is done by interview, observation and documentation using data analysis technique from data editing stage, categorical data and interpretation of data. This study resulted in the conclusion that, the first development of Islamic religious education in an effort to improve the quality of personality is a conscious effort to improve quality as an effort to create better quality through Islamic religious education in the personality of a person. Second, the supporting factors and obstacles to the development of Islamic religious education is the expected results, materials and time allocations, methods, students as learnes, interaction between parents, good education environment, religious teachers to support student success and inhibiting factors is learning the less effective, educational curriculum, methods that do not vary, the environment is not good, the limitations of infrastructure so that the management tend to be sober. Third, how to overcome the factors that hamper development of Islamic religious education is the approach must be effective, maximize the competence of teachers, methods, create a good environment, and provide school infrastructure to support learning to be more effective.